From genetic risk to early detection - clinical outcomes of a person-centered screening program for women with a high genetic risk of breast cancer - Zhou, Ke; Abadie, Caroline; Crivelli, Louise; Fortin, Euriell; Bellanger, Martine; Huet, Charlotte (Frontiers in Oncology, 2026)
BackgroundThere is little evidence on breast cancer (BC) diagnosed in women with a high genetic risk, before and after their inclusion in a long-term risk management program based on genetic risk assessment. We analyzed clinical outcomes in women enrolled in the Phare Grand Ouest (PGO) program.MethodsThe PGO includes carriers of the BRCA1 and BRCA2 pathogenic variants (PV) and women at high risk without BRCA PV, enrolled in eight cancer genetics units. The study population included all women with incident or prevalent BC, and 1:1 matching by age at first diagnosis was conducted. Multivariable generalized linear and logistic regression models were used to examine the associations between tumor size and cancer stage and the following covariates: age, tumor subtype, pathogenic variant status, prevalent/incident BC status, and healthcare accessibility indicators.ResultsWithin the matched cohort, those with incident BC were significantly younger at inclusion, but were of comparable age at the time of first diagnosis. They had smaller tumors, and the odds of advanced-stage disease were approximately 30% lower than those observed in women with prevalent BC (OR = 0.29, p < 0.01). Younger age and a triple-negative phenotype were independently associated with larger tumor size. No significant effect was shown from healthcare accessibility indicators.ConclusionThe PGO’s coordinated, person-centered approach to high genetic risk management was likely associated with earlier-stage BC detection in women with the BRCA PV and women at high risk without BRCA PV. These findings both underscore the enhanced value of person-centered surveillance programs that integrate genetic risk assessment and long-term clinical follow-up, and pave the way for further research in this area.